Two weak solutions for some singular fourth order elliptic problems - Lin Li (Electronic Journal of Qualitative Theory of Differential Equations, 2016)
In this paper, we establish the existence of at least two distinct weak solutions for some singular elliptic problems involving a $p$-biharmonic operator, subject to Navier boundary conditions in a smooth bounded domain in $\mathbb{R}^N$. A critical point result for differentiable functionals is exploited, in order to prove that the problem admits at least two distinct nontrivial weak solutions.